2002
DOI: 10.1037/0882-7974.17.1.101
|View full text |Cite
|
Sign up to set email alerts
|

Well- and ill-defined measures of everyday cognition: Relationship to older adults' intellectual ability and functional status.

Abstract: The present study examined 2 approaches to the measurement of everyday cognition in older adults. Measures differing in the degree of structure offered for solving problems in the domains of medication use, financial management, and food preparation and nutrition were administered to a sample of 130 community-dwelling older adults ranging in age from 60 to 90 (M ϭ 73 years, SD ϭ 7.02 years). Well-defined and ill-defined everyday problem-solving measures, which varied in the amount of means-end-related informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
135
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(149 citation statements)
references
References 70 publications
(158 reference statements)
12
135
1
1
Order By: Relevance
“…It is important to investigate anxiety symptoms and mood, because these emotional states may influence or be influenced by cognitive complaints and subjective attitudes toward cognitive functioning. This is in line with a controlled intervention study that van Hooren et alindicated that an experimental neuropsychological intervention program significantly reduced mood-related complaints [22]. During the course, participants practised activities encountered in real life with emphasis on the complaints and problems experienced by the participants.…”
Section: Introductionsupporting
confidence: 49%
“…It is important to investigate anxiety symptoms and mood, because these emotional states may influence or be influenced by cognitive complaints and subjective attitudes toward cognitive functioning. This is in line with a controlled intervention study that van Hooren et alindicated that an experimental neuropsychological intervention program significantly reduced mood-related complaints [22]. During the course, participants practised activities encountered in real life with emphasis on the complaints and problems experienced by the participants.…”
Section: Introductionsupporting
confidence: 49%
“…Memory predictors explain on average 1.9% of the variance in everyday functioning outcomes in the review of Royall and colleagues (2007), although the Hopkins Verbal Learning Test (HVLT; Brandt & Benedict, 2001) explains considerably more variance than average (R 2 = .14). Allaire and Marsiske (2002) reported that a verbal declarative memory factor, composed of the sum of HVLT learning Trials 1, 2, and 3, is associated with everyday cognition (standardized effect size = 0.22). This factor was in turn significantly associated with self-rated everyday functioning in a sample of community-residing older adults.…”
mentioning
confidence: 99%
“…Problem solving originated from cognitive psychology, and research in this tradition has focused more on the outcomes of problem solving and the effectiveness of solutions generated (Reitman, 1965;Simon, 1973). In addition, studies from this orientation have tended to focus on more instrumental tasks (i.e., solutions involving manipulation of data or objects in the service of selfand home-maintenance goals) and have tended to be well structured (i.e., initial state, available means/information, and desired end state are all provided to the problem solver; e.g., Allaire & Marsiske, 2002).…”
Section: A Definitional Issuesmentioning
confidence: 99%
“…A third possible area of added value is motivational; if everyday problems tasks seem relevant and familiar, they may encourage greater self-efficacy (e.g., Artistico et al, 2003) and willingness to agree to testing (Cornelius, 1984). Allaire and Marsiske (2002) investigated the first form of ''added value,'' examining whether several measures of everyday problem solving could predict everyday function (IADL and advanced IADLs) as well as, or better, than a traditional cognitive battery. Two measures, the Everyday Cognition Battery (ECB, a well-structured test of instrumental problem solving) and a solution fluency measure (for problems of food preparation, medication use, and financial management), explained more than 50% of the reliable variance in reported everyday function.…”
Section: Relationship To Everyday Functionmentioning
confidence: 99%
See 1 more Smart Citation